Optimal control-based coordinated operation strategy for fan and air conditioning systems: Balancing individual thermal comfort and energy efficiency - Lyu, Junmeng; Yang, Yuxin; Lian, Zhiwei; Du, Heng (Building and environment, 2025)
•Developed an automatic coordinated fan–air-conditioner control strategy.•The strategy enables local thermal control based on individual thermal sensations.•Surrogate models were built in a simulated environment for performance evaluation.•The strategy achieved over 20 % energy savings while maintaining neutral sensation.•Key factors affecting the operational performance of the system were analyzed. The local fan and air conditioning coordinated system (FACS) enables individualized thermal environments, which has practical significance for enhancing thermal comfort and energy efficiency. However, few studies have developed control strategies that simultaneously balance individual comfort and energy minimization. This study proposes an optimal control strategy based on individual thermal sensation models to optimize the coordinated settings of shared thermostats and local fans in both single- and multi-occupant scenarios. Subject-specific thermal sensation models were developed (R² = [0.605, 0.942]; mean absolute error = [0.17, 0.61]) and embedded within a thermophysiological model coupled with a simulated environment to construct a testing framework for strategy evaluation. Coordinated operation setpoints were computed for randomly generated occupant groupings within this framework, and their energy performance was evaluated using EnergyPlus. Results indicate that the proposed strategy enables an increase in the shared thermostat setpoint while maintaining the majority of occupants within the neutral thermal sensation range. In scenarios with 1 to 4 occupants, the developed control strategy achieved energy savings exceeding 20 % compared to A/C-only operation. Robustness tests further demonstrated that the strategy prioritized air speed adjustment and maintained stable thermostat settings under perturbations in air temperature, skin temperature, and air speed, while maintaining thermal comfort. Additionally, analysis of subject data from Shanghai revealed that when maximizing overall neutral thermal sensation, the optimal shared thermostat setpoint decreased with increasing occupant numbers, highlighting the influence of occupancy on FACS performance. This study provides a model-based solution for individualized indoor thermal regulation with enhanced energy efficiency. [Display omitted]